PERBEDAAN AKTIFITAS ANTIMIKROBA EKSTRAK GAMBIR DAN NANO-GAMBIR TERHADAP MIKROBA PENYEBAB KEPUTIHAN - Harry Ade Saputra; Shantrya Dhelly Susanty (Jurnal Endurance, 2021)
Abnormal vaginal discharge can cause serious problems if not treated properly. Gambir one of the commodities which has been used as a treatment for abnormal vaginal discharge. Nanotechnology is an emerging science which is expected to increase effectiveness of gambir. This research aims to study the difference effect between gambir-extract and gambir-nanoparticles against abnormal vaginal discharge (Candida albicans and Streptococcus mutans) microbes growth. This study was an experimental laboratory research with posttest-only comparison group design. The independent variable were variations in the concentration of gambir-extract and gambir-nanoparticles. The dependent variable was the zone of inhibition of microbes (Candida albicans and Streptococcus mutans). The data were analyzed by the normality test. After that, bivariat test had been used to see the difference significance value between variables. T Independent test variables C. albicans obtained that p value 0,00 (< 0,05). T Independent test variables S. mutans obtained that p value 0,00 (< 0,05). The conclusion of this research shows there are significant differences between gambir-extract and gambir-nanoparticles against abnormal vaginal discharge microbes growth